An Overview of the Actions of Capsaicin and Its Receptor, TRPV1, and Their Relations to Small Primary Sensory Neurons - Hiura, Akio; Nakagawa, Hiroshi (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2011)
The specific actions of capsaicin on the small primary afferent neurons with regard to neurogenic inflammation and plasma extravasation are examined in this review. First, a short history of the study of capsaicin is introduced from the viewpoint of the efferent function of capsaicin-sensitive nerve fibers. Agonist (resiniferatoxin) and antagonists (capsazepine and ruthenium red) of capsaicin are referred, to better understand the action of the drug. The significance of the discovery of capsaicin receptor, TRPV1, and its characteristic features (polymodal receptor) are discussed based on recent reports, although the sensitization or desensitization mechanisms are not yet resolved. This review also briefly deals with the therapeutic use of capsaicin and its agonist and antagonist for relief pain. Whether or not capsaicin-sensitive nerve fibers are involved in itching is examined by a recent literature survey. TRPV1- expressing nerve fibers were recently reported to be responsible for the itching sensation. Three possible itching pathways were raised. The participation of pure sensory nerve fibers which exclusively transmit itchiness has not been found, as yet.
Keywords: Axon reflex